Multiple affixations in ziggy zezsyazeoviennazabrizkie novel di tanah lada - Manik, Findi; Daeli, Prima Jaya; Manalu, Bella Renata Br; Sitompul, Roselyn Gracia; Ambarita, Esron (EDUCTUM: Journal Research, 2026)
This study investigates the phenomenon of multiple derivational affixation in the novel Di Tanah Lada by Ziggy Zezsyazeoviennazabrizkie. The research aims to identify the types of multiple affixes used in the text and to analyze their morphotactic structure as well as the resulting shifts in word class and meaning. The study employs a qualitative descriptive method, with data collected through observation and note-taking from linguistic units found in the novel. The analysis is based on Aronoff’s word-based morphology theory and Lieber’s hierarchical structure theory to explain the layered formation of complex words. The findings reveal several patterns of multiple affixation, including prefixes (meN-, ber-, pe-, ter-), suffixes (-an, -kan, -i), and confixes (ke- -an and per- -an/pe- -an). Among these, confixes appear most frequently and function primarily to form abstract nouns expressing emotional or mental states. The analysis also demonstrates that multiple affixation contributes to categorical shifts and semantic expansion in the narrative. Overall, the study highlights how the flexibility of Indonesian derivational morphology enriches the expressive and narrative quality of literary texts.